1997
DOI: 10.1007/s004010050692
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopapillary neurocytoma of temporal lobe with glial differentiation

Abstract: We present a case of cerebral neurocytoma with unusual pseudopapillary pattern, which was a predominant feature in the tumor and was characterized histologically by hyalinized vascular cores surrounded by a single or multilayered small round cells. Vascular hyalinization was also evident in the linear arborizing capillary networks in the cellular mass of the tumor. Immunohistochemically, the tumor cells were strongly positive for synaptophysin and neuron-specific enolase except some cells lining the pseudopapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Komori et al [3] first reported, in 1998, this entity as PGNT. A similar histologic case was reported by Kim and Suh [5] in 1997 as pseudopapillary neurocytoma. Papillary glioneuronal tumor is usually extraventricular with only 1 having been reported in the third ventricle [6] and is composed of glial and neuronal histologic components.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Komori et al [3] first reported, in 1998, this entity as PGNT. A similar histologic case was reported by Kim and Suh [5] in 1997 as pseudopapillary neurocytoma. Papillary glioneuronal tumor is usually extraventricular with only 1 having been reported in the third ventricle [6] and is composed of glial and neuronal histologic components.…”
Section: Discussionsupporting
confidence: 71%
“…Both the cortex and white matter may be involved, and the male/female ratio is 1:1. This number excludes the case labeled as pseudopapillary [11] 23/M L parietooccipital N 6.0 84 Broholm et al [12] 16/M L frontal --Komori et al [3,4] 13 neurocytoma [5], regarded as a variant of pseudopapillary glioneuronal tumor by Komori and Scheithauer [4]. The major differential diagnosis includes ependymoma, ganglioglioma, extraventricular neurocytic neoplasm, and dysembryoplastic neuroepithelial tumor.…”
Section: Discussionmentioning
confidence: 97%
“…A hyalinized pseudopapillary vascular pattern was reported in central neurocytomas arising from the temporal lobe by Kim et al 7 They regarded it as a distinct neoplasm because synaptophysin or NSE-positive cells were found around the vascular walls, and neither ganglioid, ganglion cells, nor astrocytic cells were found in the solid areas composed of cells with neurocytic differentiation. On the other hand, Bouvier-Labit reported one case of PGNT that showed NSE-positive and/or synaptophysin-positive cells, but no neurofilament-positive or GFAP-positive cells in 39 neurocytomatous areas.…”
Section: Discussionmentioning
confidence: 94%
“…The most common surgical complications are memory dysfunction, because of forniceal injury, and hemiparesis [2,3,[27][28][29]. Gross-total resection can be achieved in 60 to 100% of patients and recurrence is seen in up to one third of patients after subtotal resection [4,5,30,31]. Rades et al [32] found that radiotherapy after subtotal tumor removal significantly improved local tumor control but had no effect on survival of children.…”
Section: Introductionmentioning
confidence: 96%